Development of Teaching Materials for Single Variable Linear Equations and Inequality with Realistic Mathematical Approaches for Class VII Students - Afni, Nur (Lembaga Riset Mutiara Akbar, 2022)
This study aims to develop teaching materials for univariate linear equations and inequalities with a realistic mathematical approach for junior high school students to assess the effectiveness of the developed teaching materials. The purpose of this study was to determine the process of developing teaching materials in the form of LKPD using a realistic mathematical approach to Class VII SMP students. The material was developed using a 4D development model consisting of definition, design, development and dissemination, and transformed into 3D consisting of definition, design, and development. It is declared valid based on the results of the verification of the teaching material evaluation questionnaire by the validator